Energy efficiency simulation of the process of gas hydrate exploitation from flue gas in an electric power plant - Shuanshi Fan; Xi Wang; Xuemei Lang; Yanhong Wang (Natural Gas Industry B, 2017)
It is a safe and environmentally-friendly method to exploit natural gas hydrates (“hydrate”) by using flue gas (mainly including CO2 and N2) from electric power plants. So far, however, its energy consumption and energy efficiency has not been investigated thoroughly. In this paper, the process to exploit hydrates from flue gas was established. Firstly, flue gas is injected into hydrate reservoirs after it is pressurized. The hydrates in reservoirs partially experience thermal decomposition while the rest is replaced with flue gas, so CH4CO2N2 mixture is formed. Secondly, the concentrated CH4CO2 mixture is got after N2 is separated and removed by using membrane component. And thirdly, the CH4CO2 mixture is delivered to the original electric power plant. This process was simulated by using the software Aspen Plus to analyze the production/injection ratio in the process of flue gas replacement under different injection pressures, the methane replacement ratio, and the energy consumption and energy efficiency in the whole process. It is indicated that the energy in the process of hydrate exploitation from flue gas is mainly consumed at the pressurized injection stage, and the injection pressure increase correspondingly results in the increase of energy consumption at pressurization and membrane separation stages, and to some extent improves the recovery ratio of pressure energy. Besides, when the injection pressure is 5–16 MPa, the production/injection ratio in the process of flue gas replacement is 0.03–0.26, the methane replacement ratio is 19.9–56.2%, the unit energy consumption in the whole process is 2.15–1.05 (kW·h)/kgCH4, and the energy return on investment (EROI) is 7.2–14.7. It is concluded that the energy efficiency of hydrate exploitation from flue gas can be effectively improved by increasing the injection pressure in the range of 5–10 MPa.